Efektivitas Pembelajaran Berbantuan AI terhadap Hasil Belajar Siswa pada Materi Keamanan Jaringan di SMKN 1 Purwakarta - Aura Roschalina Putri; Dian Permata Sari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study investigated the comparative effectiveness of Artificial Intelligence (AI)- assisted instruction versus conventional teaching methods in enhancing students' cognitive learning outcomes regarding Network Security material. The research was conducted at State Vocational High School (SMK) 1 Purwakarta. A quantitative quasi-experimental design, specifically the Nonequivalent Control Group Design, was employed, involving 70 eleventh-grade students from the TJKT (Computer and Network Engineering) department. The research instruments comprised pretest and posttest cognitive tests. Data analysis was performed using the non-parametric Wilcoxon Signed-Rank Test to observe changes within groups, and an Independent Samples t-test on the Delta scores to compare outcomes between groups. The findings indicate that the experimental group, which received the AI-assisted intervention, experiences a substantially higher mean improvement in learning outcomes (M = 24.46) compared to the control group (M= 6.11). Furthermore, the Wilcoxon test confirms a significant enhancement in the experimental group, whereas the control group shows no statistically significant difference. The comparative analysis of Delta scores reveals a significant difference between the two groups (p < 0.05), consequently leading to the rejection of the null hypothesis (H0). These results explicitly demonstrate that the implementation of AI-assisted learning is more effective in facilitating the enhancement of students' cognitive competence in Network Security than conventional teaching methodologies.